The financial and welfare impact of household tobacco expenditure in Malaysia / Tan Wei Leong - Tan, Wei Leong (2019)
The tobacco epidemic is a public health threat in Malaysia and around the world. This project is mainly motivated by concerns about the non-health financial and welfare impact of tobacco-smoking on tobacco smokers and their households. Household tobacco expenditure was examined using data from five comparable nationally representative Household Expenditures Surveys conducted in 1993, 1998, 2004, 2009 and 2014. First part of the study estimated the household tobacco expenditure and the household tobacco expenditure share across the various living standards and the distribution of tobacco expenditure in Malaysia. The study revealed that the burden of tobacco-smoking in the country has remained persistently high whereby the proportion of tobacco expenditure at household level has always been above 35.0% over five points of time and that the middle quintile has gradually emerged as the highest consumer of tobacco between 2004 and 2014. The proportion of households with tobacco expenditure was declining between 1993 and 2009 across all consumption quintiles but resurged in 2014. Although the burden of tobacco-smoking was high, the monthly per capita adult equivalent tobacco expenditure was relatively low among tobacco-smoking households, ranging from MYR39.51 to MYR52.40. In addition, the household tobacco expenditure share of total household expenditures had reduced from 7.00% to 4.60%, which indicates that there has been a reduction in the amount of money spent for the purchase of tobacco products. From concentration curves and indices, the household tobacco expenditure is more concentrated among the richest quintile of the Malaysia population irrespective of region, urban-rural stratum and ethnicity. The second part of the study estimated the impoverishment attributable to direct tobacco expenditure in Malaysian households, as based on an increase in the estimate of the poverty headcount. While overall, there was iv impoverishment due to direct tobacco expenditure; the proportion was very small and declined from 1.08% in 1993 to 0.01% in 2014 irrespective of regions, urban-rural stratum and ethnicity. The third part of the study estimated the crowding out of essential goods and services due to tobacco expenditure. The crowding out effect was analysed using one of the consumer demand models, namely the Quadratic Almost Ideal System (QUAIDs). In addition, seemingly unrelated regression was used to estimate the crowding out effect on five expenditures groups simultaneously as each of the expenditures groups affects the others. The analysis showed that the crowding out of essential goods and services was present but very modest among tobacco-smoking households in Malaysia, where the tobacco-smoking households significantly reduce their expenditures on food(1.64% less), education(0.47% less), medical care(0.35% less), housing(1.88% less) and clothing(0.20% less) compared to non-smoking households. This observation was rather consistent across all consumption expenditures quintiles irrespective of living standards. Additionally, sub-population analysis showed that the dose-response relationship between the crowding out effects and the intensity of tobacco expenditure was present for food, medical care and housing. Overall, this study found that household tobacco expenditure in Malaysia was low and its share in total household expenditure was declining. Moreover, the impoverishment and welfare impact from direct tobacco expenditure although present, was very modest. All of the major findings of this study could be explained by the affordability of cigarettes which may be contributed by suboptimal taxation of cigarettes, rampant availability of illicit cigarettes and pace of the increase in income has exceeded the increase in the tobacco price. The main message here is that the effectiveness of tobacco taxation is intrinsically linked to the availability of illicit cigarettes and, as such, an increase in tobacco taxation must be concurrently complemented by extensive control of illicit cigarettes to ensure that action to reduce tobacco usage through the utilization of fiscal measures is effective. In light of the v foregoing, future research could concentrate on assessing the actual burden of illicit cigarettes in Malaysia as well the tobacco tax mitigation strategies to fill the knowledge gap identified in this study.